2020
DOI: 10.3389/fneur.2020.576153
|View full text |Cite
|
Sign up to set email alerts
|

Postinfectious Onset of Myasthenia Gravis in a COVID-19 Patient

Abstract: Objective: We report the case of a young woman with postinfectious onset of myasthenia gravis after COVID-19 with mild respiratory symptoms and anosmia/ageusia 1 month before admission to our neurological department. Methods: Patient data were derived from medical records of Hannover Medical School, Germany. Written informed consent was obtained from the patient. Results: The 21-year-old female patient presented with subacute, vertically shifted double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 12 publications
(11 reference statements)
3
86
1
2
Order By: Relevance
“…CSF antibodies to SARS-CoV-2 were tested in 58/414 (14%) patients who did not have a positive CSF SARS-CoV-2 PCR (49/58 (84%) of whom had symptoms that localized to the CNS and 9/58 (16%) of whom had symptoms that localized to the PNS) [ 6 , 13 , 25 , 31 , 43 , 46 , 98 , 101 , 113 , 119 , 127 , 141 , 182 , 193 , 197 , 209 , 220 , 224 , 231 , 233 , 237 , 246 ]. Of these, 42/58 (72%) tested positive for SARS-CoV-2 antibodies in the CSF [ 6 , 25 , 31 , 43 , 46 , 98 , 119 , 127 , 193 , 197 , 209 , 224 , 231 , 237 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CSF antibodies to SARS-CoV-2 were tested in 58/414 (14%) patients who did not have a positive CSF SARS-CoV-2 PCR (49/58 (84%) of whom had symptoms that localized to the CNS and 9/58 (16%) of whom had symptoms that localized to the PNS) [ 6 , 13 , 25 , 31 , 43 , 46 , 98 , 101 , 113 , 119 , 127 , 141 , 182 , 193 , 197 , 209 , 220 , 224 , 231 , 233 , 237 , 246 ]. Of these, 42/58 (72%) tested positive for SARS-CoV-2 antibodies in the CSF [ 6 , 25 , 31 , 43 , 46 , 98 , 119 , 127 , 193 , 197 , 209 , 224 , 231 , 237 ].…”
Section: Resultsmentioning
confidence: 99%
“…CSF oligoclonal bands were tested in 114 patients who did not have a positive CSF SARS-CoV-2 PCR or positive CSF antibodies to SARS-CoV-2 (103 (90%) who had symptoms that localized to the CNS and 11 (10%) who had symptoms that localized to the PNS) [ 9 , 10 , 19 , 20 , 35 , 36 , 42 , 44 , 45 , 58 , 69 , 74 , 79 , 81 , 101 , 112 , 113 , 116 , 117 , 126 , 127 , 130 , 135 , 136 , 147 , 149 , 152 , 154 , 160 , [168] , [169] , [170] , [171] , 177 , 181 , 182 , [185] , [186] , [187] , [188] , 191 , 194 , 203 , 205 , 207 , 209 , 212 , 213 , 215 , 216 , 218 , 233 , 242 , 245 ]. Of these, 35 (31%) had matched CSF and serum bands [ 9 , 35 , 79 , 112 , 113 , 127 , 147 , 170 , 171 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that α7 nAChR activation increases STAT3 phosphorylation, decreases TNF-α and IL-6 expressions, and ultimately reduces viral myocarditis, indicating that α7 nAChR agonists could be a promising new strategy for patients with viral myocarditis. Also, a recent case study documented the post-infectious onset of myasthenia gravis in a COVID-19 patient, indicating that the SARS-CoV-2 virus could be an etiological agent in this case [ 61 ]. It is well-established that myasthenia gravis is associated with the presence of AChR antibodies, although it is unclear how this could be linked to the interactions presented herein.…”
Section: Discussionmentioning
confidence: 99%